Sex differences in breathing - Gargaglioni, Luciane H. [UNESP]; Marques, Danuzia A. [UNESP]; Patrone, Luis Gustavo A. [UNESP] (Elsevier, 2019)
Breathing is a vital behavior that ensures both the adequate supply of oxygen and the elimination of CO2, and it is influenced by many factors. Despite that most of the studies in respiratory physiology rely heavily on male subjects, there is much evidence to suggest that sex is an important factor in the respiratory control system, including the susceptibility for some diseases. These different respiratory responses in males and females may be related to the actions of sex hormones, especially in adulthood. These hormones affect neuromodulatory systems that influence the central medullary rhythm/pontine pattern generator and integrator, sensory inputs to the integrator and motor output to the respiratory muscles. In this article, we will first review the sex dependence on the prevalence of some respiratory-related diseases. Then, we will discuss the role of sex and gonadal hormones in respiratory control under resting conditions and during respiratory challenges, such as hypoxia and hypercapnia, and whether hormonal fluctuations during the estrous/menstrual cycle affect breathing control. We will then discuss the role of the locus coeruleus, a sexually dimorphic CO2/pH-chemosensitive nucleus, on breathing regulation in males and females. Next, we will highlight the studies that exist regarding sex differences in respiratory control during development. Finally, the few existing studies regarding the influence of sex on breathing control in non-mammalian vertebrates will be discussed.
Keywords: Amphibian; Mammals; Respiration; Sex hormones; Sexual dimorphism